Development of a PCR test for detection of warfarin resistance based on the polymorphism of VKORC1 genes / Mohd Hafiz Mohd Saif - Mohd Saif, Mohd Hafiz (2012)
VKORC1 gene plays important role in coding for Vitamin K Epoxide Reductase for determining the warfarin resistance. Screening of polymorphism of VKORC1 before starting drug therapy as different patient will act differently to the warfarin therapy. The aim of this study is to develop and validate a PCR method for detection of polymorphism of VKORC1. Allele specific PCR together with nested PCR have been used. The product was conducted under different annealing temperature to determine the optimal annealing temperature that will be run to use in second PCR for screening patients. All parameters used in PCR is crucial in developing the PCR method. Allele specific PCR is suitable, reliable, simple rapid and more economical for PCR test for detection of warfarin resistance base on polymorphism of VKORC1.